The p38MAPK-MK2 Signaling Axis as a Critical Link Between Inflammation and Synaptic Transmission - Beamer, Edward; Corrêa, Sonia A. L. (Frontiers in Cell and Developmental Biology, 2021)
p38 is a mitogen-activated protein kinase (MAPK), that responds primarily to stress stimuli. p38 has a number of targets for phosphorylation, including MAPK-activated protein kinase 2 (MK2). MK2 primarily functions as a master regulator of RNA-binding proteins, indirectly controlling gene expression at the level of translation. The role of MK2 in regulating the synthesis of pro-inflammatory cytokines downstream of inflammation and cellular stress is well-described. A significant amount of evidence, however, now points to a role for the p38MAPK-MK2 signalling axis in mediating synaptic plasticity through control of AMPA receptor trafficking and the morphology of dendritic spines. These processes are mediated through control of cytoskeletal dynamics via the activation of cofilin-1 and possibly control of the expression of Arc/Arg3.1. There is evidence that MK2 is necessary for group I metabotropic glutamate receptors long-term depression (mGluR-LTD). Disruption of this signalling may play an important role in mediating cognitive dysfunction in neurological disorders such as fragile X syndrome and Alzheimer’s disease. To date, the role of neuronal MK2 mediating synaptic plasticity in response to inflammatory stimuli has not yet been investigated. In immune cells, it is clear that MK2 is phosphorylated following activation of a broad range of cell surface receptors for cytokines and other inflammatory mediators. We propose that neuronal MK2 may be an important player in the link between inflammatory states and dysregulation of synaptic plasticity underlying cognitive functions. Finally, we discuss the potential of the p38MAPK-MK2 signalling axis as target for therapeutic intervention in a number of neurological disorders.